Elementos del Derecho de Fundaciones - Pantoja Murillo, Carlos German (2020)
The law of foundations contains a set of elements that constitute a particular profile as an institutionalized expression of philanthropy, which distinguishes it from other legal entities. The particularity of being established based on the legal parameters, according to the founder’s will, linking assets to a social purpose; being able to develop an economic activity provided that it is directed to that purpose, being tax exempt in general, and having special transformation mechanisms has been a subject not extensively treated in our academic milieu.